Guest Associate Editor - Yiatros, Stylianos (My University, 2026)
Aims & ScopeStability and failure are two correlated phenomena in materials and structures which in engineering practice are treated as either separate or in causality. Yet, while instability may entail failure, instabilities may play a control function in, for example biomaterials or soft materials, etc. They can also enhance structural performance by allowing possible harvesting of predictive structural modes of functionality that are scalable, reversible, and robust, a process known as “Buckliphilia”. The intricate interplay between instability and failure is also critical for nanomaterials, soft materials, and some nonclassical materials such as metamaterials with designed periodic properties. This special collection of the Journal of Engineering Mechanics is dedicated to such nonclassical and nonlinear materials and structures. We invite contributions that are theoretical, experimental, or numerical in nature, or a combination thereof. Contributions investigating theories and applications for such nonclassical materials and nonlinear structures involving cross-disciplinary areas are particularly encouraged and sought. Examples include:• Instability and failure of biomaterials• Instability and failure of nanomaterials• Instability and failure of metamaterials• Instability and failure of soft materials• Instability and failure of nonlinear structures• Instabilities across scales• “Buckliphilia” or instability-driven design• Harnessing instability to enhance performanceSection Editors:C. W. Lim, City University of Hong Kong (bccwlim@cityu.edu.hk)Stylianos Yiatros, Cyprus University of Technology (stylianos.yiatros@cut.ac.cy)Ahmer Wadee, Imperial College London (a.wadee@imperial.ac.uk)